Human B-1 cells are important contributors to the naturally-occurring IgM pool against the tumor-associated ganglioside Neu5GcGM3 - Rodriguez-Zhurbenko, Nely; Quach, Tam D.; Rothstein, Thomas L.; Hernandez, Ana M. (Frontiers in Immunology, 2022)
Only few studies have described the anti-tumor properties of natural antibodies (NAbs). In particular, natural IgM have been linked to cancer immunosurveillance due to its preferential binding to tumor-specific glycolipids and carbohydrate structures. Neu5GcGM3 ganglioside is a sialic acid–containing glycosphingolipid that has been considered an attractive target for cancer immunotherapy, since it is not naturally expressed in healthy human tissues and it is overexpressed in several tumors. Screening of immortalized mouse peritoneal-derived hybridomas showed that peritoneal B-1 cells contain anti-Neu5GcGM3 antibodies on its repertoire, establishing a link between B-1 cells, NAbs and anti-tumor immunity. Previously, we described the existence of naturally-occurring anti-Neu5GcGM3 antibodies with anti-tumor properties in healthy young humans. Interestingly, anti-Neu5GcGM3 antibodies level decreases with age and is almost absent in non-small cell lung cancer patients. Although anti-Neu5GcGM3 antibodies may be clinically relevant, the identity of the human B cells participating in this anti-tumor antibody response is unknown. In this work, we found an increased percentage of circulating human B-1 cells in healthy individuals with anti-Neu5GcGM3 IgM antibodies. Furthermore, anti-Neu5GcGM3 IgMs were generated predominantly by human B-1 cells and the antibodies secreted by these B-1 lymphocytes also recognized Neu5GcGM3-positive tumor cells. These data suggest a protective role for human B-1 cells against malignant transformation through the production of NAbs reactive to tumor-specific antigens such as Neu5GcGM3 ganglioside.